Human Placenta Hydrolysate Protects Against Acetaminophen-Induced Liver Injury in Mice - Inyoung Hwang; Chi-Gu Kang; So-Jung Lim; Hyun-Jin Kim; Ryun Kang; So-Hyun Jeon; Sang-Hoon Lee; Jae-Won Kim; Ju-Seop Kang (Biomedicines)
Background/Objectives: Acetaminophen (APAP) is a widely used analgesic and antipyretic, but overdose can lead to APAP-induced liver injury (AILI), a major cause of acute liver failure. While N-acetylcysteine (NAC) is the current standard of care, its efficacy is significantly reduced when administered after the peak time of liver injury, highlighting the need for alternative therapeutic strategies. Human placenta hydrolysate (HPH) has shown potential as a therapeutic agent for various liver diseases due to its rich content of bioactive compounds. This study aimed to investigate the hepatoprotective effects of HPH in a mouse model of AILI. Methods: HPH was administered to mice for three days prior to APAP treatment. The effects of HPH on liver morphology, necrosis, liver enzymes, phase I/II detoxification enzymes, oxidative stress markers, and inflammatory cytokines were evaluated. Results: HPH pretreatment attenuated APAP-induced liver necrosis and congestion, reduced serum levels of liver enzymes. In addition, HPH showed a concentration-dependent attenuation of APAP-induced decrease in human hepatocyte viability. HPH modulated phase I/II enzyme expression by downregulating CYP2E1 and upregulating SULT1A1, UGT1A6, GSTP1, and TPMT. HPH also exhibited antioxidant effects by increasing SOD and GPx activities, reducing MDA levels, and restoring the GSH/GSSG ratio. Furthermore, HPH attenuated the APAP-induced increase in the inflammatory cytokines TNF-α and IL-6. These findings suggest that HPH protects against AILI through multiple mechanisms, including the modulation of phase I/II detoxification, activation of antioxidants, and inhibition of inflammation. Conclusions: HPH could be a potential therapeutic option for APAP overdose and related liver injuries.